Kualitas Pelayanan Izin Mendirikan Bangunan Rumah Tinggal Untuk Mewujudkan Perlindungan Hukum Masyarakat Pada Unit Pengelola Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Administrasi Jakarta Timur - Wulandari, Olivia Intan; Pitono , Andi; Ali, Haikal (UIR Press, 2025)
The purpose of this research is to determine and analyze the quality of service for Building Permit (IMB) for Residential Houses, as well as to identify and analyze the factors that support and hinder the quality of service for Residential Building Permits (IMB) in order to realize legal protection for the public at the Investment Management Unit and One-Stop Integrated Services of East Jakarta Administrative City.This research employs a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The informants in this study are the Head of the East Jakarta PMPTSP Unit, Coordinators of Service Implementation Units I and II of the East Jakarta PMPTSP, the community, community leaders, and religious figures. The data analysis in this study uses the interactive data analysis model from Miles and Huberman, which includes the following steps: 1) Data Reduction, 2) Data Presentation, 3) Drawing Conclusions. The findings of this research are: 1) The quality of service for Residential Building Permits (IMB) in terms of legal protection for the public, when viewed from aspects such as direct evidence, responsiveness, guarantees, and empathy, is still low. 2) Factors that support the quality of service for Residential Building Permits (IMB) are: a) The availability of legal frameworks, b) Community support for the department's work program, c) External support: the availability of law enforcement officers, as well as internal and external supervisors such as the Inspectorate and BPKP. Factors that hinder the quality of service for Residential Building Permits (IMB) are: a) Limited number of staff, b) Limited budget, c) Lack of community participation, d) Weak supervision of services, e) Insufficient implementation of Standard Operating Procedures (SOP), f) Delays in coordination